Alternative splicing-mediated cis-regulation in Breast Cancer Risk - Duarte, André Alexandre Rodrigues Besouro (2021)
Genome-wide association studies (GWAS) were pivotal in identifying genomic variants associated with susceptibility to breast cancer (BC). Given most identified loci are on non-coding regions, unidentified causal variants are predicted to act through cis-regulatory mechanisms. Post- GWAS era relies on functional analysis to identify causal and characterize how risk-associated variants modulate gene expression. To this end several in silico techniques are used associating molecular phenotypes with genotype but most of these focus on transcriptional processes. With this work, I analyse the potential contribution of alternative splicing (AS) altering variants in breast tissue to BC susceptibility. To this end I used RNA-seq data from healthy breast tissue with matching sample genotype. Afterwards, I employed two different packages to independently quantify AS. Splicing Quantitative Trait Loci (sQTL) analysis was performed in order to identify sQTLs, variants associated with changes in splicing patterns. BC GWAS associated single nucleotide polymorphisms (hit-SNPs) were retrieved and co-localization analysis based on ancestry-specific linkage disequilibrium was performed to assess if any of the identified sQTLs is associated with GWAS hit-SNPs. Three loci were identified where sQTLs are co-localized with BC GWAS hit-SNPs. In locus 1p36 variants rs4908724 and rs17229081 are associated with changes in splicing of PARK7, a protein deglycase previously identified as an oncogene. Regarding locus 11q13, 4 sQTLs – rs56984820, rs6591195 and rs9735063 – were identified, reporting changes in splicing patterns of BANF1, responsible for activating genome repair pathways interacting with PARP; with publications proposing as multi-cancer biomarker. Changes in ULK3 splice pattern were associated with variants rs12591513 and rs12898397 on locus 15q24. This gene is a regulator of Hedgehog pathway, whose dysregulation is associated with carcinogenesis. These changes in AS impact isoform ratios resulting in different protein and/or on UTRs, impacting other gene expression regulatory mechanisms. Further functional studies are required to identify causal variants as well as impacted cis-regulatory elements. Thus, variants may increase risk for BC modulating CRE of AS.